2012
DOI: 10.30638/eemj.2012.059
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Groundwater Quality in Some Vulnerable Areas in Botosani County for Nitrates and Nitrites Based Pollutants

Abstract: This paper emphasizes a groundwater quality assessment using thirty-seven hydro-geological drillings, located in vulnerable and non-vulnerable areas in Botosani County as regarding nitrate and nitrites based pollutants and also phosphates and ammonium, during 2001-2008. The groundwater quality from vulnerable areas is within allowed limits. It was observed a decrease of nitrates and nitrites concentration in four locations designated as vulnerable zones regarding nitrates. In non-vulnerable areas, the groundwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Four different initial concentrations, mentioned in Section 2.2, were used to assess the capability of kaolin on nitrate adsorption. The percentage and the amount of nitrate adsorption at equilibrium concentration for all initial concentrations were calculated using (1) and (2), which are shown in Table 2. Table 2 revealed that initial nitrate concentration has an effect on the amount of nitrate adsorption at equilibrium.…”
Section: Effect Of Initial Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Four different initial concentrations, mentioned in Section 2.2, were used to assess the capability of kaolin on nitrate adsorption. The percentage and the amount of nitrate adsorption at equilibrium concentration for all initial concentrations were calculated using (1) and (2), which are shown in Table 2. Table 2 revealed that initial nitrate concentration has an effect on the amount of nitrate adsorption at equilibrium.…”
Section: Effect Of Initial Concentrationmentioning
confidence: 99%
“…Groundwater and soil can be polluted through various anthropogenic activities such as pesticide use and industrial processes [1]. The breaking of the ecological equilibrium between human being and the nature is the main reason of environmental contamination issue [2]. Since 1970s nitrate leaching to subsoil has become an important environmental quality and human health issue, especially due to high use of nitrogen as nutrient in agriculture [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, because of the different mineralogical nature of the base clay (composed of kaolinite, montmorillonite, chlorite, halloysite, illite, vermiculite, smectite, pyrophyllite, etc.) and of the firing technology, but also the foundations, plasticizers and other additives employed in the manufacturing, the acid-basic character, given by the marginal groups, varies widely, from weakly acidic (pH ≤ 4,5) to weakly alkaline (pH ≤ 9,5) [1,2,3,4,5,6]. An important role in the capacity for ionic exchange is that of the porosity and, respectively, the active surface area of the granulite’s.…”
Section: Introductionmentioning
confidence: 99%
“…In urban water systems, the concentrations of metallic species, nutrients and organic matter are, in general, several times higher than levels found in other stretches of a nonurbanized river, and may express significant damages to the ecosystem [14][15][16][17][18][19]. Metallic species differ from organic pollutants because they are not degradable and may accumulate in organisms and environmental compartments influencing their toxicity [20][21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%